Tetrahydrobiopterin Administration Augments Exercise-Induced Hyperemia and Endothelial Function in Patients With Systemic Sclerosis - Machin, Daniel R.; Clifton, Heather L.; Wray, D. Walter; Frech, Tracy M.; Donato, Anthony J. (Frontiers in Medicine, 2022)
Systemic sclerosis (SSc) is a rare, auto-immune disease with variably progressive fibrosis of the skin and internal organs, as well as vascular dysfunction. Recently, we demonstrated a decrement in exercising skeletal muscle blood flow and endothelium-dependent vasodilation in SSc, but the mechanisms responsible for these impairments have not been investigated. Thus, we sought to determine if acute administration of tetrahydrobiopterin (BH4), an essential cofactor for endothelial nitric oxide synthase (eNOS), would improve hyperemia and brachial artery vasodilation during progressive handgrip exercise in SSc. Thirteen patients with SSc (63 ± 11 years) participated in this placebo-controlled, randomized, double-blind, crossover study. Tetrahydrobiopterin (10 mg/kg) administration resulted in a 4-fold increase in circulating BH4 concentrations (P < 0.05). Cardiovascular variables at rest were unaffected by BH4 (P > 0.05). During handgrip exercise, BH4 administration increased brachial artery blood flow (placebo: 200 ± 87; BH4: 261 ± 115 ml/min; P < 0.05) and vascular conductance (placebo: 2.0 ± 0.8; BH4: 2.5 ± 1.0 ml/min/mmHg; P < 0.05), indicating augmented resistance artery vasodilation. Tetrahydrobiopterin administration also increased brachial artery vasodilation in response to exercise (placebo: 12 ± 6; BH4: 17 ± 7%; P < 0.05), resulting in a significant upward shift in the slope relationship between Δ brachial artery vasodilation and Δ shear rate (placebo: 0.030 ± 0.007; BH4: 0.047 ± 0.007; P < 0.05) that indicates augmented sensitivity of the brachial artery to vasodilate to the sustained elevations in shear rate during handgrip exercise. These results demonstrate the efficacy of acute BH4 administration to improve both resistance and conduit vessel endothelial function in SSc, suggesting that eNOS recoupling may be an effective strategy for improving vasodilatory capacity in this patient group.